2019
DOI: 10.1002/fsn3.962
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐obesity and hypolipidemic effect of water extract from Pleurotus citrinopileatus in C57BL/6J mice

Abstract: Obesity has become one of the most important health problems worldwide requiring urgent need for efficient control. Pleurotus citrinopileatus ( P. citrinopileatus )—a type of edible mushroom with abundant bioactive molecules—is a promising source for achieving this goal. In the present study, we evaluated the anti‐obesity and hypolipidemic effect of P. citrinopileatus water extract ( PWE ) using a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…The increase in the concentration of mycelial extract and the prolong treatment exposure significantly reduced the food intake of the nematodes, which suggest a loss of appetite and/or suppression of overeating. This observation is consistent with the recent study of Sheng et al [37], who reported that water extract from mushroom Pleurotus citrinopileatus significantly decreased the food intake resulting to the reduction of weight gain and fat accumulation in highfat diet-fed C57BL/6J mice. In addition, Khatun et al [38] reported that feeding of edible mushroom Echigoshirayukidake supplemented chow (5% w/w) significantly reduced the food intake and prevented body weight gain, fat deposition in the viscera, and hyperlipidemia in genetically defined obese model rat.…”
Section: In-vitro Activity Of L Strigosus Mycelial Extract In C Elesupporting
confidence: 93%
“…The increase in the concentration of mycelial extract and the prolong treatment exposure significantly reduced the food intake of the nematodes, which suggest a loss of appetite and/or suppression of overeating. This observation is consistent with the recent study of Sheng et al [37], who reported that water extract from mushroom Pleurotus citrinopileatus significantly decreased the food intake resulting to the reduction of weight gain and fat accumulation in highfat diet-fed C57BL/6J mice. In addition, Khatun et al [38] reported that feeding of edible mushroom Echigoshirayukidake supplemented chow (5% w/w) significantly reduced the food intake and prevented body weight gain, fat deposition in the viscera, and hyperlipidemia in genetically defined obese model rat.…”
Section: In-vitro Activity Of L Strigosus Mycelial Extract In C Elesupporting
confidence: 93%
“…Fungi are known to produce a wealth of bioactive secondary metabolites and have a wide range of applications in agriculture, industrial, pharmaceuticals, and biomedical sectors (Fouda, Hassan, Eid, & Ewais, ; Sheng et al, ). To date, over 750 new metabolites from fungi have been described between 1993 and 2013, which confirms the tremendous potential of the fungal secondary metabolome (Keller, ).…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account that lipid-lowering drugs are the main strategy in treating atherosclerosis and that their side effects are important [7,8,10], the search for new hypolipidemic drugs with fewer side effects has drawn great attention in recent years [11,12]. In this context, some plants have been studied for their lipid-lowering effect in animal and human models [12,13]. The principal reason in interest on plants is their effectiveness in traditional medicine as remedy for dyslipidemia and cardiovascular complications [14].…”
Section: Introductionmentioning
confidence: 99%